POST-COAL MINING LAND SUITABILITY BASED ON FOOD PROVIDER ECOSYSTEM SERVICES DATA IN TANAH LAUT REGENCY - Riena Arrizqi Muhardini; Dienny Redha Rahmani; Kiky Permana Setiawan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Activities before and after coal mining have both positive and negative impacts. So this requires a change in post-mining function, where post-mining land can become a useful or productive area. This study uses qualitative research methods. Data collection techniques are by observing the existing conditions of post-coal mining land. Other data collection comes from data on ecosystem services for food providers in Tanah Laut Regency. The analytical method used is descriptive qualitative. It can be concluded that post-coal mining land in Tanah Laut Regency has the potential to become agricultural and plantation areas. The review is based on data on ecosystem services that provide food, namely the form of land is classified as medium, which means that the land can be used for food needs, taking into account land-use methods.